EFEK PELATIHAN DAN PENDAMPINGAN TERHADAP PENGEMBANGAN USAHA MELALUI MEDIASI KREATIFITAS - Qiftih, Kurnia Mariatul; Alam, Syamsul Alam; Muhammadin, Ahkmad (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
The purpose of this study is to analyze the influence of training and mentoring on business development mediated by creativity in business actors guided by the inspirational young entrepreneur community of South Sulawesi, South Sulawesi. This type of research is descriptive research with a quantitative approach. The sample in this research were business actors assisted by the South Sulawesi Inspirational Young Entrepreneur Community, totaling 44 umkm. The data analysis method used is descriptive statistical analysis and path analysis. The research results show that training has an insignificant positive effect on business development. Mentoring has a significant positive effect on business development. Creativity has a significant positive effect on business development. Training has a significant positive effect on creativity. Mentoring has a significant positive effect on creativity. Creativity is able to mediate the relationship between training and business development. Creativity is able to mediate the relationship between training and business development.